Bismuth Nanobowl/Bismuth Oxides, a Hybrid Material for Efficient Adsorption and Visible‐light‐driven Photodegradation of Organic Pollutants. Issue 2 (16th January 2020) - Pan, Tao; Feng, Weihua; Cheng, Cong; Lin, Sili; Fang, Jianzhang; Zhu, Ximiao; Chen, Yi; Fang, Zhanqiang
Abstract: To achieve the goal of efficient organic pollutants removal, bismuth nanobowl (Bi) /bismuth oxides was rationally designed and synthesized. In the Bi/bismuth oxides, BiOCl/Bi2 O2.33 was covered on the surface of Bi nanobowls after etching bowl‐shaped bismuth (previously prepared by solvothermal method with the addition of D‐Fructose) with hydrochloride acid solution. Compared to the one without etching, the obtained Bi/bismuth oxides nanobowls with enlarged surface area lead to remarkable enhancement in dye adsorption. The rhodamine B (RhB) adsorption behavior over the Bi/bismuth oxides samples all fitted pseudo‐second‐order model. Adsorption is a crucial previous step for photocatalysis. Due to the high adsorption capacity and the synergistic effect between surface oxides and plasmonic Bi, the Bi/bismuth oxides nanobowls exhibited high removal efficiency for organic pollutions under visible light irradiation. Abstract : Bismuth nanobowl/bismuth oxides was successfully prepared by etching reaction with hydrochloride acid. Compared to the one without etching, the prepared catalyst exhibited significant improved specific surface area and adsorption owing to special hollow structures. Photocatalytic perform for rhodamine B and 2, 4‐Dichlorophenol can also be improved because of synergistic effect between surface oxides and plasmonic Bi. It is a promising strategy to remove practical organic pollutants by this design method of photocatalyst.